Nano‐Theranostic Modality for Visualization of the Placenta and Photo‐Hyperthermia for Potential Management of Ectopic Pregnancy. Issue 2 (17th November 2022) - Moses, Abraham S.; Kadam, Leena; St Lorenz, Anna; Baldwin, Maureen K.; Morgan, Terry; Hebert, Jessica; Park, Youngrong; Lee, Hyelim; Demessie, Ananiya A.; Korzun, Tetiana; Mamnoon, Babak; Alani, Adam W. G.; et al.
Abstract: Ectopic pregnancy (EP) is the leading cause of maternity‐related death in the first trimester of pregnancy. Approximately 98% of ectopic implantations occur in the fallopian tube, and expedient management is crucial for preventing hemorrhage and maternal death in the event of tubal rupture. Current ultrasound strategies misdiagnose EP in up to 40% of cases, and the failure rate of methotrexate treatment for confirmed EP exceeds 10%. Here the first theranostic strategy for potential management of EP is reported using a near‐infrared naphthalocyanine dye encapsulated within polymeric nanoparticles. These nanoparticles preferentially accumulate in the developing murine placenta within 24 h following systemic administration, and enable visualization of implantation sites at various gestational stages via fluorescence and photoacoustic imaging. These nanoparticles do not traverse the placental barrier to the fetus or impact fetal development. However, excitation of nanoparticles localized in specific placentas with focused NIR light generates heat (>43 °C) sufficient for disruption of placental function, resulting in the demise of targeted fetuses with no effect on adjacent fetuses. This novel approach would enable diagnostic confirmation of EP when current imaging strategies are unsuccessful, and elimination of EP could subsequently be achieved using the same nano‐agent to generate localized hyperthermia resulting in targeted placental impairment. Abstract : The developed nano‐theranostic modality has potential for placenta imaging and management of ectopic pregnancy. Systemically injected nanoparticles preferentially accumulate in the placenta, allowing for accurate visualization with fluorescence and photoacoustic imaging. If ectopic pregnancy is detected, these nanoparticles are capable of generating heat upon exposure to near‐infrared light, impairing placental function and thereby inducing the demise of the associated fetus.